Historical dictionary of the People's Republic of China - Sullivan, Lawrence R. (Historical dictionaries of Asia, Oceania, and the Middle East, 2016)
Examination of important Chinese personalities and aspects of China's politics, economy, foreign relations, religion, and culture.